Accessibility Analysis of Disdukcapil Websites for Persons With Disabilities Using WCAG 2.2 - Rifqi Akbar; Debi Irawan; Ismail Ismail; Tia Luthfia Annisa (Dinasti International Journal of Education Management and Social Science, 2025)
The rapid development of information technology has encouraged governments to adopt digital systems to improve the quality of public services, particularly through the implementation of e-Government at the Department of Population and Civil Registration (Disdukcapil) of West Java Province. However, the effectiveness of digital services is not only determined by the availability of information but also by the level of accessibility that ensures equality for all users, including persons with disabilities. This study aims to evaluate the accessibility of Disdukcapil websites across 18 regencies and cities in West Java using Site Analyzer and AudioEye tools, based on the Web Content Accessibility Guidelines (WCAG) 2.2 standards. The findings reveal that most websites fall into the moderate category in terms of design and accessibility, but remain weak in search engine optimization and content quality. The AudioEye audit identified recurring accessibility issues, including unlabeled links and buttons, missing skip links, unlabeled form fields, disordered headings, and interactive elements without proper identification. These violations not only create technical barriers but also have psychological impacts on users with disabilities, such as frustration, mental fatigue, anxiety, and feelings of exclusion in digital interactions. The study underscores that failure to meet accessibility standards is not merely a technical issue but also reflects a form of social exclusion that re-duces the quality of life for vulnerable groups. Therefore, the development of Disdukcapil websites must prioritize the gradual implementation of WCAG 2.2, improve navigation struc-tures, and provide consistent labeling to realize inclusive, effective, and sustainable digital public services.